Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445319
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion Vault: the Extra Mile in Analyzing VR Locomotion Techniques

Abstract: Figure 1: Features of the Locomotion Vault interactive database and visualization include: fltering by attributes (left image), an animated gallery with individual technique descriptions for over 100 locomotion techniques (middle), and two similarity graphs that are expert-created or calculated from the attributes (right).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 24 publications
(23 reference statements)
0
23
0
1
Order By: Relevance
“…Research should expand by exploring interfaces that include body movements such as stepping, leaning, and arm movements, going beyond basic walking and body rotation. The concordance framework could provide a useful taxonomy to distinguish interfaces presented within the Locomotion Vault [3]. Furthermore, research on the interaction between locomotion interfaces and piloting cues should identify the critical features of useful environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…Research should expand by exploring interfaces that include body movements such as stepping, leaning, and arm movements, going beyond basic walking and body rotation. The concordance framework could provide a useful taxonomy to distinguish interfaces presented within the Locomotion Vault [3]. Furthermore, research on the interaction between locomotion interfaces and piloting cues should identify the critical features of useful environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…They also found higher embodied locomotion cues for walking rather than sitting. Among other research studies focusing on interaction techniques, locomotion, and embodiment (e.g., Zielasko et al, 2016;Weise et al, 2019;Di Luca et al, 2021), Lages and Bowman (2018) focused on the effect of manipulating objects vs physically walking in the virtual environment on performance in demanding visual tasks. They found that in designing the learning environments, the creator should consider the user controller experience, past gaming experience, and spatial ability of the user.…”
Section: Sense Of Embodimentmentioning
confidence: 99%
“…Many different techniques for locomotion have been developed [18,31,33,37,39,44], but in this work we focus on the RDW technique developed by Razzaque et al [34]. A recent review of VR locomotion interfaces can be found in [24]. By slowly rotating or translating the VE around the user while they walk, RDW allows users to explore virtual environments while located in smaller physical environments [33].…”
Section: Prior Work and Backgroundmentioning
confidence: 99%